Effects of soaking, autoclaving and roasting on the nutritional composition, antinutritional factors and functionality of carob seed germ meal - Fadel, Abdalbast H. I.; Kamarudin, Mohd Salleh; Ebrahimi, Mahdi; Romano, Nicholas Paul; Saad, Che Roos; Samsudin, Anjas Asmara @ Ab Hadi (Faculty of Engineering, Universiti Putra Malaysia, 2016)
The effects of soaking, autoclaving or roasting on the nutritional composition (proximate and mineral), antinutritional factors (total phenol, tannin composition, phytic acid, saponin, and trypsin inhibitors), and functionality (water/oil absorption capacity, foaming capacity, foam stability and nitrogen solubility) of carob seed germ meal (CSGM) were studied. For the soaking treatments, CSGM was immersed in distilled water for 12 or 24 h. For autoclaving treatments, CSGM was autoclaved to 121°C for 15 or 30 min while for roasting treatments, CSGM was heated to 130°C for 20 or 40 min. Crude protein and fiber increased significantly when 30 min autoclaved. Antinutritional factors and minerals in CSGM decreased significantly in all pretreatments, but particularly when 30 min autoclaved. All pretreatments significantly decreased CSGM functionality, but autoclaving had the greatest effect. Overall, soaking seemed to provide the best balance between preserving the nutritional composition, reducing the antinutritional factors and minimizing the loss of CSGM functionality.